PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN MELALUI MATERI KEWARGANEGARAAN DI SEKOLAH - Sri Hartati; Mestika Pudan Purba; Sri Yunita; Reh Bungana Br Perangin-angin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Instilling environmental character is very important considering the increasing environmental degradation due to human actions. As a foundation in education, elementary schools play a strategic role in instilling character values ​​in students, one of which is through Citizenship Education (PKn) learning. This study aims to explain how PKn material can be used as an effective means of forming environmental character among elementary school students. The method used in this study is a case study with a descriptive qualitative approach. The subjects of the study consisted of class teachers and fourth grade students of UPT SD Negeri 060910. Data collection was carried out through observation, interviews, and documentation. The results of the study showed that PKn material related to Pancasila values ​​and the rights and obligations of citizens can be integrated with environmental issues through contextual learning. Teachers utilized a thematic approach as well as discussion methods, projects, and direct activities such as community service and waste recycling. As a result, students showed increased awareness of the environment through daily behavior, such as disposing of garbage in its place and saving energy. This study concluded that the integration of citizenship material with environmental issues has proven effective in fostering environmental character among elementary school students. Therefore, support is needed from the curriculum and training for teachers so that this integration can take place optimally and sustainably.